Chronological Age and Puberty Coping Strategy Among Iranian Adolescent Females - Mahnaz Akbari Kamrani; Malihe Farid (Shiraz University of Medical Sciences, 2017)
Background: The speed and magnitude of physical, mental, social, and emotional changes during adolescence result in stress. Improper coping strategies toward stress have a negative impact on the mental health of adolescents that may continue to their adulthood. Objectives : The present study aimed at investigating puberty coping strategies, puberty knowledge, and attitude of early and late adolescent females living in Karaj, Iran. Methods: This was an analytical cross-sectional study conducted on 513 female high school students using the multi-stage random sampling method. The Persian form of Endler and Parker coping inventory for stressful situations, the scale for the assessment of knowledge and attitudes of adolescent females towards puberty, and socio-demographic questionnaire were used to gather data. The SPSS v21 and Chi-square, Kruskal Wallis, and Spearman were used to analyze data at a significance level of 0.05. Results: The average age of participants was 15.40 (± 1.52).Results showed that avoidance was the dominant puberty coping strategy and the least frequent was related to the problem-focused strategy. A significant difference was observed between the frequency of coping strategies (P = 0.001), knowledge status (P ≤ 0.001) and attitude (P = 0.005) towards puberty, and source of information for puberty (P ≤ 0.001) was shown between two age groups of 15 years and under and above 15. Conclusions: The findings of this study showed the significance of educating teen females about physical and psychological changes during puberty. It seems that health educators and health practitioners could help young females cope with puberty through training proper coping strategies. Parents should also be educated to be supportive and should be able to consider puberty as a stressful situation and help adolescents with proper coping.